Comparative Effectiveness of Student Team Achievement Division and Team Assisted Instruction on Grade 10 Students’ Performance in Polynomial Functions - Nester Jade U. Baggas; Francis Brylle V Barila; John Patrick P. Villastiqui (Ar-Riyadhiyyat: Journal of Mathematics Education, 2026)
This study examined the comparative effectiveness of Student Team Achievement Division (STAD) and Team Assisted Instruction (TAI) in improving Grade 10 students’ performance in illustrating polynomial functions and writing polynomials in standard form. Grounded in cooperative learning theory, a quantitative quasi-experimental counterbalanced repeated-measures design was employed involving 20 Grade 10 students from a public secondary school during the 2024–2025 academic year. Descriptive statistics and paired-samples t-tests were used to analyze post-test scores, while structured classroom observations assessed learning behaviors. Results indicated that both STAD and TAI produced high levels of mathematics achievement. Although TAI yielded slightly higher mean scores, the differences were not statistically significant at the 0.05 level, with only small effect sizes observed. Behavioral findings demonstrated consistently high levels of participation, collaboration, attentiveness, and persistence under both instructional conditions. The results suggest that shared cooperative learning mechanisms, positive interdependence, individual accountability, peer explanation, and scaffolding, may exert a stronger influence on achievement than procedural differences between models. Despite limitations related to sample size and the absence of a pre-test, the study provides context-specific evidence supporting the effectiveness of structured cooperative learning in secondary algebra instruction.